Tacite et implicite : une caractérisation des productions langagières didactiques et de leurs enjeux épistémiques - Christian Dépret; Jean-Philippe Maitre (Recherches en Éducation)
In common sign exchanges, many signs are used as if their meaning was a shared obviousness. The teacher cannot only assume the comprehension of what he says by the students (especially when it regards key notions). When he uses a sign for the very first time, what it designates cannot be immediately understood by them. Comprehension shall occur indirectly, only on the basis of other signs which signification is supposedly known. Consequently, we see that one of the tasks of the teacher is to control the students’ semiotic environment. In this paper, we develop a theoretical reflexion to enlighten the way teacher may deal with this responsibility. We will first acquaint with various acceptation of what is a sign, insisting on its relation with the knowledge of the person that uses it. In a second part, it will lead us to present the notions of tacit and implicit. Finally, in a third part, we will see to underline didactical phenomena and problems that these notions may help consider in the teacher speech